Kinetic Absorption of CO₂ from Motor Vehicle Exhaust Gas Using K₂CO₃ (Potassium Carbonate) Absorbent in a Bubble Column Reactor - Raihan Nur Awwabin; Muhammad Yerizam; Erwana Dewi (Journal of Engineering Science and Technology Management, 2026)
This study investigates the kinetics of CO₂ absorption from motor vehicle exhaust using potassium carbonate (K₂CO₃) as an absorbent in a jet bubble column reactor. The research aims to analyze the effect of process variables on reaction rate constants and CO₂ conversion efficiency. Employing a pure experimental method, the study was conducted at the Chemical Engineering Laboratory, Sriwijaya State Polytechnic, from August to July 2024. The population comprised all absorption processes using K₂CO₃, with purposive sampling applied to select experimental conditions. Key instruments included a jet bubble column reactor, gas analyzer, and supporting equipment. Data analysis utilized descriptive statistics and quantitative comparison across variable treatments. Results revealed that optimal CO₂ absorption occurred at a gas flow rate of 0.3–0.4 L/min, liquid flow rate of 0.6–0.7 L/min, temperature of 40°C, and K₂CO₃ concentration of 0.04 M, yielding the highest reaction rate constant and CO₂ conversion. The study concludes that optimizing process variables is crucial for enhancing reactor performance, while further research is recommended to address scale-up and equipment limitations.